Competências emocionais em adultos praticantes de Mindful Self-Compassion, mindfulness e não praticantes - Camargo, Bruna da Mota (2025)
The present study aimed to investigate emotional competencies assessed through emotional intelligence measures using both self-report and performance-based instruments, among three groups: individuals trained in Mindful Self-Compassion (MSC), mindfulness practitioners, and non-practitioners. The instruments used included the Revised Emotional Competence Inventory (ICE-R), the Emotional Regulation Test (TRE), and the Self-Compassion Scale (SCS). The results indicated that the MSC-trained group scored higher on most emotional intelligence factors measured by the ICE-R instrument compared to the other groups. In contrast, no significant differences were observed between groups in the performance-based measures of the TRE. Spearman correlations revealed a strong association between self-compassion and self-reported emotional intelligence, particularly in the factors of mindfulness, self-kindness, and emotional perception, while correlations with performance-based measures were weak. This research contributes to the understanding of emotional intelligence and the effects of mindfulness and MSC training, providing a foundation for further studies on mindfulness training programs for the general public.